Ketidakpercayaan dan Pemberontakan: Suatu Kajian Eksegesis atasBilangan 14:1-10 - Ferderiko Budiman; Hendi Hendi (Jurnal Teologi Amreta (ISSN: 2599-3100), 2025)
The sin of disbelief in God is manifested in resistance. Resistance to divine authority is defined as rebellion. When practiced by a few, it can affect many others. Numbers 14:1-10 provides an illustrative example of Israel's lack of belief in God's promise and subsequent rebellion. Those who engage in willful rebellion will face consequences. The objective of this article is to elucidate that unbelief that culminates in rebellion is a sin. To surmount unbelief, it is essential to exercise vigilance against negative information and to fortify one's faith. The exegesis method is employed to interpret four layers of meaning in the Bible: the literal translation, semantic content, moral knowledge, and anagogic or sanctification. The authors posit that unwavering faith is a prerequisite for trusting God, as a lack of such faith may precipitate a descent into unbelief and rebellion against Him.